Late-Onset Isolated Corticotrope Deficiency in a Woman with Down Syndrome - Ibtissem Oueslati; Marwa Ben Jemaa; Meriem Yazidi; Fatma Chaker; Melika Chihaoui (Case Reports in Endocrinology)
Isolated corticotrope deficiency is a rare cause of secondary adrenocortical insufficiency. Its occurrence in patients with Down syndrome is exceptional. Herein, we report a case of an isolated corticotrope deficiency diagnosed at the age of 33 years in a woman with Down syndrome and discuss its possible mechanisms. A 33-year-old woman with Down syndrome was referred to our department for the investigation of low blood pressure. She complained of asthenia, dizziness, and palpitation with arterial hypotension for the past 4 years. The thyroid function was normal and anti-thyroperoxidase antibodies were negative. The peak of cortisol level in response to the insulin-induced hypoglycemia test was 9.4 μg/dl. ACTH level was normal, indicating corticotrope deficiency. Other pituitary hormones were normal. Magnetic resonance imaging scan revealed a partially empty sella turcica. Genetic analysis showed no mutations and no copy number variants of the TBX19 and NFKB2 genes. The mechanism of isolated corticotrope deficiency is unclear, but it may be induced by autoimmune mechanism in similar to other disorders of patients with Down syndrome.